Characterization of Tribo-corrosion using jatropha curcas linnaeas biodiesel for automotive engine component materials - Maleque, Md. Abdul; Ani, Mohd Hanafi; Samat, Noorasikin; Ahmed, Abu Saleh; Rahman, Md Mustafizur (2016)
Biodiesel as an alternative renewable fuel is increasingly being considered as blending components or replacement for traditional petroleum fuels. It consists of different ester molecules with variable levels of unsaturations and chain lengths. Although the acceptance of biodiesel in automobile applications is relatively a successful story, questions continue to arise with regards to its materials incompatibility and degradation properties. With compared to diesel, biodiesel is more prone to absorb water and permits the development of electrochemical corrosion processes. Therefore, the aim of this study was to characterize the tribological and corrosion behaviour of automotive engine component materials using Jatropha curcas linnaeus (JCL) biodiesel. The use of JCL biodiesel in this study for wear and corrosion characterization is quite new. A thorough laboratory investigation on tribo-corrosion behavior of biodiesel has been performed in order to evaluate and characterize the bio-compatibility of automotive engine component materials especially AISI 4340 alloy steel and CP-Ti with and without coating under JCL biodiesel at different process variables such as temperature, load, speed, current density etc. From the results it was found that JCL biodiesel has great impact on the control of wear and corrosion. Moreover, materials characterization after tribo-corrosion test showed that the main mechanisms or phenomenon for the wear are abrasive, corrosive and pitting. However, TiC coated alloy steel showed improved wear resistance as this alloy steel demonstrated lower wear volume loss as compared to the uncoated steel in presence of Jatropha biodiesel at higher temperature. Based on the current study, it is preferable to use alloy steel with TiC coating in automotive applications that use biodiesel fuel.